Chaos-assisted broadband momentum transformation in optical microresonators - Jiang, Xuefeng; Shao, Linbo; Zhang, Shu-Xin; Yi, Xu; Wiersig, Jan; Wang, Li; Gong, Qihuang; Lončar, Marko; Yang, Lan; Xiao, Yun-Feng (Science (American Association for the Advancement of Science), 2017)
The law of momentum conservation rules out many desired processes in optical microresonators. We report broadband momentum transformations of light in asymmetric whispering gallery microresonators. Assisted by chaotic motions, broadband light can travel between optical modes with different angular momenta within a few picoseconds. Efficient coupling from visible to near-infrared bands is demonstrated between a nanowaveguide and whispering gallery modes with quality factors exceeding 10 million. The broadband momentum transformation enhances the device conversion efficiency of the third-harmonic generation by greater than three orders of magnitude over the conventional evanescent-wave coupling. The observed broadband and fast momentum transformation could promote applications such as multicolor lasers, broadband memories, and multiwavelength optical networks.